SUSTAINABILITY OF BELAT FISHING GEAR USE IN SUNGAI GAYUNG KIRI VILLAGE, RANGSANG SUBDISTRICT, MERANTI ISLANDS REGENCY - Simanjuntak, Tia Srimulia; Sari, T Ersti Yulika; Nasution, Polaris (Departemen PSP IPB, 2025)
Sungai Gayung Kiri Village in Rangsang Subdistrict, Meranti Islands Regency, has great fisheries potential, with most of the community relying on capture fisheries using traditional fishing gear such as belat (set nets). This area has experienced severe coastal abrasion, which has led to mangrove degradation, shifts in fishing grounds, and a decline in catch production. This research was conducted in 2025 in the coastal waters of Sungai Gayung Kiri. The purpose of this study was to determine the sustainability status of belat fishing gear based on ecological, economic, and technological dimensions. The method used in this study was a survey method through direct field observation and interviews with fishermen. The data collected included the number of fishing units, production trends, environmental parameters, and sustainability attributes. The data were analyzed using Multidimensional Scaling (MDS) with the RAPFISH approach. The results showed that the ecological dimension had a value of 20.02%, categorized as unsustainable. The economic and technological dimensions obtained values of 58.34% and 57.99%, respectively, and were categorized as moderately sustainable. This study concludes that although belat remains an important traditional fishing gear, its sustainability is still low, particularly in the ecological aspect. The findings indicate the need for sustainable fisheries management, including mangrove conservation, regulated resource utilization, and improved fishing gear technology. Key words: coastal abrasion, fisheries sustainability, mangrove, RAPFISH, set net